Liras into Lyres: Talking Across Difference in the Works of Edith Nesbit - Melissa Jenkins (Cahiers Victoriens et Edouardiens)
This article’s title references a conversation between the Bastable siblings at the start of Edith Nesbit’s The New Treasure-Seekers (1904), the third title in her Bastable trilogy, which also includes The Story of the Treasure-Seekers (1899) and The Wouldbegoods (1901). In a chapter called ‘The Road to Rome’, the children imagine leaving England, although none of the children make it past the London train station, and only one travels farther than the family sitting room. As Oswald presents this conversation to the reader, he watches himself as a participant in the conversation, and takes time to annotate it for the reader, revealing small details about the children’s reactions and relations to each other. The conversation, and many like it across Nesbit’s novels, unfolds the extent to which the children’s speech comes into conflict with adult conventions, and the extent to which conversation fuels their understanding of their own nation and other lands. My analysis uncovers how conversations between children in Nesbit’s novels feature partial knowledge, constructed piecemeal through misunderstandings and mishearings. The primary claim that emerges from the analysis is that linguistic and conversational errors, within the conversations between children about travel, fuel a brand of radical cross-cultural sympathy, and that this sympathy challenges adult perceptions about race and nation. I agree that any account of a child’s agency can be overstated, even within Nesbit’s works. Yet, I posit that this focus on mishearings and misunderstandings restores unexpected power to the child’s speech, especially when the child is speaking to other children. Being unable (or unwilling) to understand an adult’s verbal directive can be liberating, and a child’s verbal play can have an effect on the adult world and even on the adult perspective. The mistakes found in the child’s acts of narration and perception present familiar places from new perspectives. To understand the phenomenon, it is helpful to draw on the distinctions between ‘localized utopia’ and ‘heterotopia’, as theorized by Michel Foucault, M. Christine Boyer, and others. As I have detailed in other work on place in children’s literature, the concept of the ‘localized utopia’ acknowledges how a subgroup may imaginatively transform one place into another. Heterotopias are spaces that are legible to children and adults alike; they are similar to localized utopias in that they mark their inhabitants as resisting social norms for defining what places mean and represent. Both can perform important social work. These acts of willful or accidental mis-seeing become even more powerful when they can be shared–when others can join in the subversive misinterpretation.